The Effectiveness of Audiobook in Teaching Reading Comprehension to Ninth Grade Students of MTs Pesantren Al Amin Mojokerto in Academic Year 2021 / 2022 - Galuh Margaretha; Irham Miftakhul Jannah (JELP Journal of English Language and Pedagogy, 2022)
The objective of the research is to measure the effectiveness of Audiobook in teaching reading comprehension to ninth grade students of MTs Pesantren Al Amin Mojokerto in academic year 2021 / 2022. The researcher conducted a quantitative research through pre-experimental design with One-Group Pretest-Posttest design. For the instrument research, researcher used pretest and posttest to collect the data. The researcher took one class of ninth grade students that contain of thirty-two students. The researcher took five meeting for this research. First meeting was giving the pretest, second until forth meeting were giving the treatment, and fifth meeting was giving posttest. In this research, the researcher used t-test sample for analyzing the data. The result show that there is different mean score between pretest and posttest. The mean score of pretest is 65,94 and the mean score of posttest is 79,97. For the t-test result, it gained higher than t-table. The t-test result is 6,71 while the result of t-table for df=31 is 1,695 in significance 5% (0,05). It proved that the result is significant. From the result, it can be concluded that teaching reading comprehension for narrative text by using Audiobook is successfully implemented for ninth grade students of MTs Pesantren Al Amin Mojokerto in academic year 2021/2022.